Условия эффективного обеспечения параметров надежности и ресурса гибочных штампов - Мельничук, Александр Владимирович; Гришин, Владимир Сергеевич; Морозенко, Елена Петровна; Трунов, Юрий Николаевич (НТУ "ХПИ", 2017)
На базе анализа общих подходов прогнозирования, процессов критического износа поверхностных слоев нагруженных деталей с учетом особенностей их эксплуатации, показана потребность проведения предварительно-подготовительных исследований перед проектированием, изготовлением, эксплуатацией ремонтом и утилизацией. С этой целью проведено деление поверхностей матрицы на функциональные элементы по уровням глубины технологии изготовления. Выявлены закономерности, которые в значительной степени определяют выбор вида и возможного варианта технологического воздействия на всех уровнях деления, для каждого элемента в соответствии с его функциональным назначением.

In this article, we show the need of preliminary research before designing, manufacturing, operation activity, repairing and utilization. Our research is based on general approach of critical worn prediction of top layers of loaded parts with consideration of their operational features. There was held dividing of matrix surface to functional elements according to the level of their manufacturing technology. Providing of prespecified functional parameters of quality and bending stamps resource are important tasks of toolroom manufacture. These parameters are influenced by stamps forming parts – matrixes and stamping punches, which functional parameters have to be provided on stage of new part producing and repairing of produced parts. Technology of realized researches could be used in manufacture conditions for worn prediction of stamp forming parts. Results are applicable not only for considered type of die stamp, but for all types of bending stamps in manufacture, because of bending stamps elem ents conformity.
Effective maintenance conditions of reliability parameters and resource of bending dies
Keywords: формообразующие детали; износ; функциональные элементы; прогнозирование; ресурс; forming parts; deterioration; functional elements